Relationship of Mesofauna Bioiversity and Undergrowth Vegetations in Jobolarangan Forest - SUGIYARTO SUGIYARTO; MARTINUS PUJO; NUR SIH MIATI (Biodiversitas Journal of Biological Diversity, 2001)
Soil mesofauna is one group of soil biodiversity, which take main role of decomposition processes of organic matter. The objective of this research was to investigate the composition and diversity of soil mesofauna at Jobolarangan forest. Soil samples were collected from 8 sampling points which different vegetation types. Soil mesofaunas extracted by modified Barless-Tullgren extractor apparatus for 4 days. The results showed that in the north side of Jobolarangan forest were identified 6 groups of microarthropods, i.e.: Mesostigma and Astigma (Ordo: Acarina), Isotomidae (Ordo: Collembola), Rhinotermitidae (Ordo: Hymenoptera), Staphyllinidae and Carabidae (Ordo: Coleoptera). The group with highest density and wide distribution was Astigma. There were high diversities of soil mesofauna community structure at Jobolarangan forest.Â© 2001 Jurusan Biologi FMIPA UNS SurakartaKey words: soil mesofauna, biodiversity, Jobolarangan forest.